Present situation of in-service detection technology of mine-used integrated protection devices and its development - LIU Tian-ye; ZHANG Zhi-jie (Gong-kuang zidonghua, 2013)
The paper pointed out problems of in-service detection technology of mine-used integrated protection devices in China such as some standards are difficult to operate, various types and models of integrated protection devices with fast update, introduced development course of mine-used integrated protection devices in China and characteristics of general detection devices, described present situation of in-service detection technology of mine-used integrated protection devices in China, proposed its development tendency in improving detection precision and automation level, higher fault analysis ability, more environmentally friendly, closer integration of computer and detection system, intelligent BIT technology and standardization.